Dublin System of Regulations: History and Contents - M. M. Biryukov; J. M. Aliyev (Московский журнал международного права, 2018)
Introduction. In this article the authors examine in detail the criteria and mechanisms for determining the Member State responsible for examining an asylum application lodged in the EU. Regulation of this area called “Dublin system”, which is one of the directions of building the Common European Asylum System in the EU.Materials and methods. The materials for the article were the works of Russian and foreign researchers in the field of international law and European law on forced migration in the EU. The methodological basis of the research consists of general scientific and special methods: dialectical method, methods of analysis and synthesis, deduction and induction, comparative legal and historical legal methods.Research results. As a result of the study the authors outline that Dublin system is part of the Common European Asylum System, which in turn is an integral part of the EU's goal of building the Area for Freedom, Security and Justice (AFSJ). The authors systematize the definitions and legal acts which form the basis of the Dublin system. On the basis of the current acts of EU, aspects of the Dublin system are analyzed, such as the criteria on the basis of which the Member State responsible are determined, the mechanism for early warning and the role of EU’s institutions in this field.Discussion and conclusions. The authors point out that the EU continues its policy of developing the Dublin system. The criticism of the Dublin system is an integral part of the deepening of integration processes in the EU. This process will be implemented by expanding the range of regulated issues and strengthening the role of supranational regulation in this field.